Never tell [compact disc, unabridged] - Burke, Alafair (Brilliance Audio, 2012)
While investigating the suicide of sixteen-year-old Julia Whitmire, whose famous parents believe that she was murdered, NYPD Detective Ellie Hatcher discovers that Julia was engaged in a dangerous game of cyberbullying against an unlikely victim.